Retaliasi Sebagai Variabel Moderasi Antara Komitmen Profesional Dan Sikap Machiavellian terhadap Whistleblowing Intention - Nicky Gervinda Putri; Dwi Suhartini (Ekonomis: Journal of Economics and Business, 2022)
Academic fraud is still an important phenomenon to be researched. The purpose of this study was to examine the effect of professional commitment, machiavellian attitude on whistleblowing intention and retaliation as moderating variables. This study uses a quantitative approach with the subject of analysis being the accounting students of UPN "Veteran" East Java Class of 2018 and 2019 totaling 100 students. The data analysis technique used WarpPLS 7.0. This study proves that the implementation of the whistleblowing system at UPN "Veteran" East Java is strongly supported by the professional commitment and machiavellian attitude of students, and reinforced by the attitude of retaliation of accounting students at UPN "Veteran" East Java. This illustrates that prospective graduates of the accounting department at UPN “Veteran” East Java have high integrity as graduates from the state defense campus.